Living-donor fresh parathyroid tissue allotransplantation as treatment for permanent hypoparathyroidism: case report - Daniel Duarte Gadelha; Wellington Alves Filho; Marjorie Azevedo Jales Brandão; Claudia Maria Costa de Oliveira; Catarina Brasil d'Alva; Virgínia Oliveira Fernandes; Renan Magalhães Montenegro Junior (Revista de Medicina da UFC, 2021)
Introduction: the standard hypoparathyroidism treatment consists of replacing calcium and active vitamin D (calcitriol), but it does not correct the underlying abnormality, parathyroid hormone (PTH) deficiency. Both the disease and its treatment are responsible for many morbidities that affect multiple organs and systems. Therefore, parathyroid allotransplantation has been described as an alternative treatment option, especially in refractory cases. Objectives: to verify if parathyroid allotransplantation is effective as a treatment for permanent hypoparathyroidism. Methodology: fresh parathyroid tissue was obtained from a 36-year-old male with a past medical history of hyperparathyroidism secondary to end-stage renal disease and immediately implanted in the recipient’s non-dominant forearm, a 57-year-old female with refractory hypoparathyroidism, despite high doses of calcium and calcitriol replacement. Corticosteroid immunosuppression was performed for 10 days. Results: the allograft showed no evidence of functionality eleven months after transplant. The procedure was considered safe. Conclusion: more studies are required to validate this technique and improve its results.